Education Level, Energy Intake and Protein With Nutritional Status Of Pregnant Women In Bungoro Health Center Work Area - Khaeriya Megauleng; Mustamin Mustamin; Sunarto Sunarto (Jurusan Gizi Poltekkes Kemenkes Makassar, 2018)
Education influences a changes in knowledge, attitudes, and lifestyle patterns in the selection of the type and amount of food consumed. The health of a pregnant women affects the fetus in her womb. Nutrient content consumed by the mother will be absorbed by the fetus which is important for the growth of the fetus itself. This study aims to determine the relationship of education level, energy intake and protein nutritional status of pregnant women in the Bungoro Health Center Work Area of Bungoro District, Pangkep Regency. This research is an analytical study with cross-sectional design. Samples were pregnant women, amount to 40 people. The level of education is obtained through a questionnaire. Energy and protein intake was obtained through 2x24 hours recall and then processed using menu A software. To find out the relationship between variables of education level, energy and protein intake with nutritional status, Chi-Square was tested using the SPSS program. Data is presented in the form of tables and narratives. The results showed that 77.5% of the sample education level was high. Sample energy intake was classified as less than 82.5% and 17.5% classified as good. Sample protein intake of 95% classified as poor and 5% classified as good. Nutritional status of pregnant women is 70% experiencing KEK and 30% normal. Statistical test results show that there is no relationship between education level, energy and protein intake and nutritional status of pregnant women in the Bungoro Health Center Work Area, Bungoro District, Pangkep Regency.